Association of BRCA2 K3326* With Small Cell Lung Cancer and Squamous Cell Cancer of the Skin. (14th May 2018) - Rafnar, Thorunn; Sigurjonsdottir, Gudbjorg R; Stacey, Simon N; Halldorsson, Gisli; Sulem, Patrick; Pardo, Luba M; Helgason, Hannes; Sigurdsson, Stefan T; Gudjonsson, Thorkell; Tryggvadottir, Laufey; Olafsdottir, Gudridur H; Jonasson, Jon G; et al.
Abstract: Background: Most pathogenic mutations in the BRCA2 gene carry a high risk of hereditary breast and ovarian cancer (HBOC). However, a stop-gain mutation, K3326* (rs11571833), confers risk of lung cancer and cancers of the upper-aero-digestive tract but only a modest risk of breast or ovarian cancer. The Icelandic population provides an opportunity for comprehensive characterization of the cancer risk profiles of K3326* and HBOC mutations because a single mutation, BRCA2 999del5, is responsible for almost all BRCA2 -related HBOC in the population. Methods: Genotype information on 43 641 cancer patients and 370 971 control subjects from Iceland, the Netherlands, and the United States was used to assess the cancer risk profiles of K3326* and BRCA2 999del5 . BRCA2 expression was assessed using RNAseq data from blood (n = 2233), as well as 52 tissues reported in the GTEx database. Results: The cancer risks associated with K3326* are fundamentally different from those associated with 999del5 . We report for the first time an association between K3326* and small cell lung cancer (odds ratio [OR] = 2.06, 95% confidence interval [CI] = 1.35 to 3.16) and squamous cell carcinoma of the skin (OR = 1.69, 95% CI = 1.26 to 2.26). Individuals homozygous for K3326* reach old age and have children. Unlike BRCA2 999del5, the K3326* allele does not affect the level of BRCA2 transcripts, and the allele is expressed to the same extent as the wild-type allele. Conclusions: K3326* associates primarily with cancers that have strong environmental genotoxic risk factors. Expression of the K3326* allele suggests that a variant protein may be made that retains the DNA repair capabilities important to hormone-responsive tissues but may be less efficient in responding to genotoxic stress.